ANALYSIS OF THE EFFECT OF LEADERSHIP BEHAVIOR AND ORGANIZATIONAL CULTURE ON THE QUALITY OF PUBLIC SERVICES IN THE LOCAL GOVERNMENT OF GORONTALO PROVINCE - Yuliani Solihin, Dwi Indah; Wahab Podungge, Abdul; Aneta, Asna (Iapa Proceedings Conference, 2025)
Public service is one of the main pillars in realizing good governance. However, in many regions, including Gorontalo Province, service quality still faces various challenges such as low responsiveness of officials, slow bureaucracy, and suboptimal public satisfaction. This condition emphasizes the urgency of conducting a study on internal organizational factors, particularly leadership behavior and organizational culture, which are believed to play an important role in improving public service quality. This study aims to analyze the influence of leadership behavior and organizational culture on the quality of public services within the Gorontalo Provincial Government. The method used is a survey with a mixed methods approach, involving 73 respondents randomly selected from a total population of 270 employees, supported by qualitative data through interviews, observations, and documentation studies. The results of the study show that leadership behavior contributes significantly to improving the quality of public services by 25.2%, while organizational culture has an influence of 31%. Simultaneously, these two variables contribute 73.2% to the quality of public services, with the remainder being influenced by other factors. These findings imply that strengthening transformational leadership and developing a positive organizational culture are key strategies for realizing responsive, transparent, and accountable public services at the local government level.